2021
DOI: 10.25259/sni_700_2020
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of venous pressure gradient in a patient with idiopathic intracranial hypertension after ventriculoperitoneal shunt placement: A proof of secondary cerebral sinovenous stenosis

Abstract: Background: The relationship between idiopathic intracranial hypertension (IIH) and cerebral sinovenous stenosis (CSS) remains unclear. The effects of cerebrospinal fluid (CSF) diversion on venous sinus physiology have not been rigorously investigated. We describe the effect of ventriculoperitoneal shunt (VPS) placement on sinovenous pressures in the setting of IIH and CSS. Case Description: A patient in their 30 s presented with headache and transient visual obscurations for few months and was diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…CSF divergence can be the logical step to reduce the disturbed balance between secretion and drainage of CSF, with an increase in total intracranial fluid content, to compensate for other possible links such as intracerebral venous and glymphatic system compression secondary to intracranial hypertension, but also large venous sinus compression with extrinsic stenosis. This secondary venous sinus stenosis can lead to a further increase in ICP, which creates a vicious cycle where the increase in ICP produces a worsened secondary sinus stenosis and higher venous pressure [ 51 , 54 ]. There is evidence that drainage of CSF with a reduction of ICP can also reverse the transverse sinus collapse in patients with idiopathic intracranial hypertension [ 54 , 55 ].…”
Section: Management Of Iihmentioning
confidence: 99%
See 1 more Smart Citation
“…CSF divergence can be the logical step to reduce the disturbed balance between secretion and drainage of CSF, with an increase in total intracranial fluid content, to compensate for other possible links such as intracerebral venous and glymphatic system compression secondary to intracranial hypertension, but also large venous sinus compression with extrinsic stenosis. This secondary venous sinus stenosis can lead to a further increase in ICP, which creates a vicious cycle where the increase in ICP produces a worsened secondary sinus stenosis and higher venous pressure [ 51 , 54 ]. There is evidence that drainage of CSF with a reduction of ICP can also reverse the transverse sinus collapse in patients with idiopathic intracranial hypertension [ 54 , 55 ].…”
Section: Management Of Iihmentioning
confidence: 99%
“…This secondary venous sinus stenosis can lead to a further increase in ICP, which creates a vicious cycle where the increase in ICP produces a worsened secondary sinus stenosis and higher venous pressure [ 51 , 54 ]. There is evidence that drainage of CSF with a reduction of ICP can also reverse the transverse sinus collapse in patients with idiopathic intracranial hypertension [ 54 , 55 ].…”
Section: Management Of Iihmentioning
confidence: 99%
“…Brain swelling from acute brain injury may negatively impact on venous drainage through compression of the large venous sinuses, particularly the sagittal and transverse sinuses. 48 , 52–54 The ICP waveform and the brain PPG changes seen with raised ICP are likely to represent prolonged systolic brain volume expansion due to a mismatch between arterial blood flow in and limited venous flows out. The ICP waveform peak is therefore delayed with a dominant P2.…”
Section: Discussionmentioning
confidence: 99%
“… 55 Studies have demonstrated that augmenting venous drainage resolves these ICP waveform changes and reduces the ICP. 48 , 52–54 …”
Section: Discussionmentioning
confidence: 99%
“…6 The mechanistic underpinnings of IIH remain poorly understood. Fundamentally, VSS has been both shown to persist in patients with resolved intracranial hypertension through pharmacologically driven decreased CSF production and resolve in others with CSF removal [16][17][18] This highlights our limited understanding of the progression and causes of IIH, specifically as it relates to VSS. Recent evidence suggests that in some cases VSS plays a significant role as either a primary or a secondary mechanism of impaired outflow.…”
Section: Discussionmentioning
confidence: 99%